Structure and share of satellite TV channels and DTH platforms in Europe - Jaksic, Krsto; Milosevic, Ivana; Jaksic, Branimir; Maksimovic, Vladimir; Todorovic, Jelena (Acta Scientiarum. Technology, 2022)
This work deals with the structure of TV channels that are distributed from satellite positions where DTH platforms offer their services in European countries. The structure is being considered via service availability (FTA and PAY TV), resolution (SDTV, HDTV and UHDTV), standards of broadcasting (DVB-S and DVB-S2), satellites and satellite positions, as well as market share of leading satellite operators at European market through which DTH providers do their services to the ultimate users. We also represent the market of TV channel distribution through the number of household which use cable, satellite, terrestrial and IPTV. Collected data are represented as a table and graph for the period from 1996 to 2020.